Patient journey in erosive oesophagitis: real-world perspectives from US physicians and patients - Colin W Howden; Stuart J Spechler; Christian Atkinson; Michael F Vaezi; Stephen Brunton; A Mark Fendrick; Corey Pelletier; Rinu Jacob (BMJ Open Gastroenterology)
Objective Management of erosive oesophagitis (EE) remains suboptimal, with many patients experiencing incomplete healing, ongoing symptoms, and relapse despite proton pump inhibitor (PPI) treatment. The Study of Acid-Related Disorders investigated patient burden of individuals with EE in a real-world setting.Design US gastroenterologists (GIs) or family physicians (FPs)/general practitioners (GPs) treating patients with EE completed a physician survey and enrolled up to four patients with EE for a patient survey, with prespecified data extracted from medical records.Results 102 GIs and 149 FPs/GPs completed the survey; data were available for 73 patients (mean age at diagnosis, 45.4 years). Omeprazole was healthcare professional (HCP)-preferred first-line treatment (60.8% GIs; 56.4% FPs/GPs), and pantoprazole preferred second line (29.4% and 32.9%, respectively). Price and insurance coverage (both 55.5% HCPs) and familiarity (47.9%) key drivers for omeprazole; insurance coverage (52.0%), price (50.0%), familiarity (48.0%), initial symptom relief (46.0%), and safety (44.0%) key drivers for pantoprazole. Only 49.3% patients took medication as instructed all the time; 56.8% independently increased medication frequency some of the time. Despite treatment, 57.5% patients experienced heartburn and 30.1% regurgitation; heartburn was the most bothersome symptom. 58.9% patients believed that their symptoms could be better controlled; only 28.3% HCPs were very satisfied with current treatment options. 83.6% patients wanted long-lasting treatment options. Fast symptom relief for patients was a top priority for 66.1% HCPs, while 56.6% would welcome alternatives to PPIs.Conclusion This real-world multicentre study highlights the need for new, rapidly acting treatments in EE that reduce symptom burden, offer durable healing and provide symptom control.